RALSTONIA SOLANACEARUM: FEATURES OF BIOLOGY AND IDENTIFICATION - Р. В. Грицай; Л. Д. Варбанець (Mìkrobìologìâ ì Bìotehnologìâ, 2012)
Ralstonia solanacearum – a causative agent of bacterial wilt for a wide range of plants, with a significant area of geographic distribution. Having South American origin, the agent has demonstrated the phenomenal adaptive properties during the second half of the 20th century, spreading and adapted to the conditions of all continents except the polar latitudes. This pathogen has the greatest economic importance among potato bacterial agents, being a subject to quarantine for Europe and Ukraine. The review highlighted the issues regarding the features of biology, taxonomy, pathogenic properties of Ralstonia solanacearum and modern methods of diagnosis and combating with the disease as well.